Food safety consortium - Vanier, M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In recent years, food safety has become an issue of concern for the beef industry, beef processors, and the consuming public. Even though America has the safest and most wholesome food supply in the world, consumers are worried about the safety of the meat they eat. In response to reports of illness from contamination by both microbes and chemicals in the meat supply, the United States Congress, in 1988, authorized and funded a Special Grants Program in the United States Department of Agriculture called the Food Safety Consortium. The members of the Consortium are Kansas State University, the University of Arkansas-Fayetteville and Iowa State University.
Keywords: Beef; Food safety; Meat